Bank Financial Performance with Bank Size as Moderation - Khosim, Nur; Masman, Ronnie Resdianto (Riviera Publishing, 2026)
This study is motivated by the importance of banking financial performance as an indicator of the success of the intermediation function and the stability of the financial sector, particularly in the context of the Indonesian banking industry, which faces dynamic competition, risk management challenges, and increasing efficiency demands. This research aims to analyze the effect of the Loan-to-Deposit Ratio, Asset-to-Equity Ratio, Total Deposits-to-Total Assets Ratio, Capital Adequacy Ratio, and Asset Growth Ratio on Return on Assets, as well as to examine the role of Bank Size as a moderating variable in these relationships. This study employs a quantitative approach. The data used are secondary data obtained from the financial statements of banks listed on the Indonesia Stock Exchange and publications issued by the Financial Services Authority during the research period, which were then analyzed using panel data regression and moderated regression analysis. The results show that, partially, the Loan-to-Deposit Ratio, Asset-to-Equity Ratio, Total Deposits-to-Total Assets Ratio, Capital Adequacy Ratio, and Asset Growth Ratio do not have a significant effect on Return on Assets. In addition, Bank Size has not been proven to significantly moderate the relationship between all independent variables and Return on Assets. Nevertheless, the research model simultaneously indicates that the variables examined are related to bank profitability. The conclusion of this study emphasizes that banking profitability is not solely determined by internal financial ratios and bank size but is also influenced by other factors outside the research model.